Retail Internationalisation process: a case study of Tesco in China - ZHOU, YUJIA (2014)
In the past several decades, there are volumes of researches on the international retailing process, focusing on different perspectives, such as scale, the motivations, entry modes, international retail learning, specific markets and unique frameworks. Due to insufficient analysis in the UK retailer, Tesco, as well as the possibility of developing a new integrated framework, this paper has developed a new comprehensive framework for the retail internationalisation process. Further to this, this paper analyses and discusses Tesco